(E)-4-(5-Hydroxy-2-methylbenzylideneamino)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one - Ming-Hua Yang; Yun-Fa Zheng (Acta Crystallographica Section E, 2008)
The title compound, C19H19N3O2, is a Schiff base compound derived from 4-aminoantipyrine and 5-hydroxy-2-methylbenzaldehyde. The molecule adopts a trans configuration about the central C=N bond. There is an intramolecular O—H...N hydrogen bond. Futhermore, weak C—H...O hydrogen bonds lead to the formation of a chain developing parallel to the b axis.